NEGOTIATING IDEAL PIETY IN DIGITAL AGE: A MIXED-METHODS STUDY ON MUSLIM CYBER ETHICS IN INDONESIA - Jannah, Raudotul; Al Ayubi, Sholahuddin (Universitas Islam Negeri Mataram, 2025)
This study investigates the ethical dissonance between ideal Islamic piety and digital behavior among Indonesian Muslims. Employing a mixed-methods approach, the research draws on quantitative data from over 100 Muslim academics and qualitative insights from 15 in-depth interviews and digital ethnography. Findings reveal a gap between ethical awareness and practice in digital spaces, particularly misinformation sharing, viral trends, and uncritical engagement with religious influencers. Furthermore, the study highlights a shift in religious authority from institutional scholars to popular digital preachers, not always grounded in scholarly credibility. The concept of adaptive piety is introduced as a context-sensitive ethical response to digital challenges. The study contributes to contemporary Islamic ethics by offering a grounded framework that bridges normative Islamic principles with the sociotechnical complexities of the Global South.